Zespół rowka nerwu łokciowego - ocena efektów leczenia operacyjnego = Cubital tunnel syndrome - evaluation of the effects of surgical treatment - Kamila Woźniak; Dorota Ratuszek-Sadowska; Maciej Śniegocki (Kazimierz Wielki University, 2016)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Śniegocki Maciej. Zespół rowka nerwu łokciowego - ocena efektów leczenia operacyjnego = Cubital tunnel syndrome - evaluation of the effects of surgical treatment. Journal of Education, Health and Sport. 2016;6(9):315-322. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61845 http://ojs.ukw.edu.pl/index.php/johs/article/view/3804       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.     Zespół rowka nerwu łokciowego - ocena efektów leczenia operacyjnego   Cubital tunnel syndrome - evaluation of the effects of surgical treatment     Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Maciej Śniegocki1   • 1.        Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu • 2.        Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu       Streszczenie   Wstęp Zespół rowka nerwu łokciowego jest to zespół chorobowy wywołany uciskiem na nerw łokciowy. Choroba najczęściej jest konsekwencją zwężenia kanału łokciowego (struktura anatomiczna utworzona przez nadkłykieć przyśrodkowy kości ramiennej, więzadło ramienno-łokciowe i rozcięgno położone pomiędzy głowami zginacza łokciowego nadgarstka). Przyczynami zwężenia są urazy, stany zapalne lub zmiany zwyrodnieniowe stawów. Cel pracy Celem niniejszej pracy była ocena efektów leczenia operacyjnego u pacjentów z zespołem rowka nerwu łokciowego bezpośrednio po zabiegu operacyjnym oraz w okresie 14 dni po zabiegu operacyjnym. Materiał i metody W okresie od stycznia 2012 roku do czerwca 2016 roku w Klinice Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej Szpitala Uniwersyteckiego nr 1 w Bydgoszczy do zabiegu operacyjnego zakwalifikowano 20 chorych, u których stwierdzono jednostronny zespół rowka nerwu łokciowego o różnym stopniu nasilenia. Badanie skuteczności metody operacyjnej obejmowało ocenę obiektywnych i subiektywnych objawów klinicznych w okresie po zabiegu operacyjnym - w 1 i 14 dobie. Wyniki Analiza dotychczasowych wyników leczenia wykazała, że po zastosowanej metodzie u większości pacjentów następuje zmniejszenie bądź ustąpienie dolegliwości bólowych i zaburzeń wegetatywnych w obszarze zaopatrywanym przez nerw łokciowy oraz poprawa funkcji chorej ręki. Wnioski Zastosowane leczenie operacyjne jest skutecznym postępowaniem u chorych, u których zostały wyczerpane możliwości leczenia farmakologicznego oraz fizjoterapeutycznego. Ocena zależności efektów terapii wymaga dalszych badań na większej liczbie pacjentów.   Słowa kluczowe: zespół rowka nerwu łokciowego, nerw łokciowy, leczenie operacyjne     Abstract   Introduction Cubital tunnel syndrome is a syndrome caused by compression of the ulnar nerve. The disease is most often the consequence of stenosis of the elbow (anatomic structure created by the medial epicondyle of the humerus, elbow-ligament brachiocephalic and aponeurosis situated between the heads of the flexor carpi ulnaris). The causes of stenosis are injuries, inflammation or degenerative arthritis. Aim of study The aim of this study was to evaluate the effects of surgical treatment of patients with cubital tunnel syndrome directly after surgery and during the 14 days after surgery. Materials and methods From January 2012 to June 2016 in the Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery, Dr Antoni Jurasz University Hospital No.1 in Bydgoszcz 20 patients diagnosed with unilateral cubital tunel syndrome with varying degrees of severity were qualified to the surgery. Study the effectiveness of surgical method included an evaluation of objective and subjective clinical symptoms in the period after surgery - on 1 and 14 day. Results The analysis of the treatment results showed that the method used the majority of patients following a decrease or disappearance of pain and disorders vegetative in the area supplied by the ulnar nerve and improve the function of diseased hand. Conclusions The applied surgical treatment is an effective procedure for patients who have exhausted the possibility of pharmacological treatment and physiotherapy. The rating is based on the effects of the therapy needs further study on a larger number of patients.   Key words: cubital tunnel syndrome, ulnar nerve, surgical treatment